Combatting jihadist terrorism through nation-building : a quality-of-life perspective /: a quality-of-life perspective. ([2019]) - Sirgy, M. Joseph; Estes, Richard J; El-Aswad, el-Sayed, 1949-; Rahtz, Don R
No abstract available